2018
DOI: 10.1071/fp18039
|View full text |Cite
|
Sign up to set email alerts
|

Optimising the linear electron transport rate measured by chlorophyll a fluorescence to empirically match the gross rate of oxygen evolution in white light: towards improved estimation of the cyclic electron flux around photosystem I in leaves

Abstract: The cyclic electron flux (CEF) around photosystem I (PSI) was discovered in isolated chloroplasts more than six decades ago, but its quantification has been hampered by the absence of net formation of a product or net consumption of a substrate. We estimated in vivo CEF in leaves as the difference (ΔFlux) between the total electron flux through PSI (ETR1) measured by a near infrared signal, and the linear electron flux through both photosystems by optimised measurement of chlorophyll a fluorescence (LEFfl). Ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 22 publications
(23 reference statements)
0
4
0
Order By: Relevance
“…We cannot eliminate the possibility that the lack of a change in CEF is due to a decrease of linear electron transport under FL, since ETR(II) also decreased (Figure 3b). In addition, it is difficult to estimate CEF by calculating ETR changes when plants are grown under a light intensity about 300 μmol photons m −2 s −1 because the ratio of CEF to LEF is very low (Zhang, Fan, Sun, & Chow, 2018). However, we found a rapidly disappearing PIR within 1 day of FL treatment, indicating a decrease of NDH‐CEF under FL conditions (Essemine et al, 2016; Figure 2g, Figure S8g).…”
Section: Discussionmentioning
confidence: 99%
“…We cannot eliminate the possibility that the lack of a change in CEF is due to a decrease of linear electron transport under FL, since ETR(II) also decreased (Figure 3b). In addition, it is difficult to estimate CEF by calculating ETR changes when plants are grown under a light intensity about 300 μmol photons m −2 s −1 because the ratio of CEF to LEF is very low (Zhang, Fan, Sun, & Chow, 2018). However, we found a rapidly disappearing PIR within 1 day of FL treatment, indicating a decrease of NDH‐CEF under FL conditions (Essemine et al, 2016; Figure 2g, Figure S8g).…”
Section: Discussionmentioning
confidence: 99%
“…Under low actinic irradiance (< 500 µmol photons m −2 s −1 ), Kou et al (2013a) showed that ETR2 can be equated to ; further, at low actinic irradiance, the matching of ETR2 with is independent of the spectral distribution of the excitation light (Zhang et al 2018). in the present study is the gross oxygen evolution rate during illumination recorded by MIMS multiplied by four (since four electrons are released for each oxygen molecule evolved).…”
Section: Methodsmentioning
confidence: 99%
“…Data of Zhang et al . (2018) and Ver Sagun et al . (2019) suggested that cyclic electron transport around PSI increased with increasing I abs .…”
Section: Introductionmentioning
confidence: 95%